Comparison of the Effectiveness of Therapist-Assisted Couple Therapy and Emotion-Focused Couple Therapy on Psychological Well-Being, Negotiation Enhancement, and Aggression Reduction in Women Victims of Spousal Violence - Javaheri, Mohammad Hossein; Aghayousefi, Alireza; Sobhi Gharamaleki, Naser (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This research aimed to compare the effectiveness of therapist-assisted couple therapy and emotion-focused couple therapy on psychological well-being, negotiation enhancement, and aggression reduction in women victims of spousal violence. Methods: The study was applied, field-based, and quasi-experimental, employing a pre-test, post-test design with a control group. The sample consisted of couples attending counseling and psychotherapy centers in Qom during the second half of 2021. Out of these, 45 couples were randomly assigned after entry criteria control into three groups: emotion-focused treatment group (15 couples), therapist-assisted treatment group (15 couples), and a control group (15 couples). The research tools included the Strauss et al. (1979) Conflict Tactics Scales and the Ryff (1989) Psychological Well-Being Scales, which were administered to the female victims in three phases: pre-test, post-test, and follow-up. The emotion-focused group received Johnson’s (2003) training package over nine sessions, and the therapist-assisted group received Aghayousefi et al.’s (2020) training package over eight sessions. The control group received no intervention. Data were analyzed using repeated measures ANOVA and SPSS software version 26. Findings: Results showed that both emotion-focused and therapist-assisted couple therapies significantly reduced aggression (F = 90.30, p < .001), increased negotiation (F = 64.47, p < .001), and enhanced psychological well-being (F = 103.81, p < .001) in the female victims of spousal violence, with these effects maintained at follow-up. However, the emotion-focused therapy package was more successful in improving psychological well-being, negotiation, and reducing aggression than the therapist-assisted therapy package. Conclusion: The findings suggest that both emotion-focused and therapist-assisted couple therapies are effective interventions for resolving conflicts and improving psychological well-being.